Mastitis in goats: A comprehensive systematic review and meta-analysis of prevalence and the pathogens - Tibebu, A.; Teshome, Y.; Tamrat, H.; Bahiru, A.; Yitbarek, T.; Moliso, Mesfin M.; Assefa, Ayalew (Elsevier, 2026)
Mastitis poses a significant challenge in the dairy industry, carrying economic, legal, public health, and animal welfare implications. The disease is primarily caused by pathogens and exacerbated by environmental, management, and host-related factors. However, comprehensive evidence synthesis remains limited compared to other livestock. Therefore, this review aims to bridge this gap by updating the prevalence and associated pathogens of mastitis in goats. We conducted systematic searches following PRISMA guidelines and, through established eligibility criteria, retrieved records retrieved filtered and screened. Quantitative data obtained from qualified studies were analysed using a random effects model. The overall estimated prevalence of mastitis was 30.6% (95% CI: 28.1–34.3%; I² = 97. 9%). The prevalences of clinical mastitis and subclinical mastitis were estimated at 7.5% (95% CI: 5.4–10.2%) and 31.6% (29.34–33.3%). Subgroup prevalence was 26.1% at udder half level and 36.1% at bulk tank level. Single summary pooled prevalence at goat level was highest in Australia (35%) and lowest in North America (11.6%). A decreasing trend was observed for udder half-level and overall mastitis prevalence, while goat-level mastitis showed an increasing trend. Major pathogens associated with goat mastitis were Staphylococcus, Streptococcus, E. coli, Klebsiella, Corynebacterium, and Pseudomonas. Staphylococcus species accounts about 30% of mastitis, with non-Staphylococcus aureus species at 20% and Staphylococcus aureus at 11%. This review highlights goat mastitis as a significant challenge in the increasingly demand of dairy goat industry. Addressing and mitigating risk factors for goat mastitis with a view to reducing the prevalence is vital for dairy goat productivity.